Establishment of Normal Reference Intervals for CD3+, CD4+, CD8+, and CD4+ to CD8+ Ratio of T Lymphocytes in HIV Negative Adults from University of Gondar Hospital, North West Ethiopia. (17th November 2014) - Gize, Addisu; Mathewos, Biniam; Moges, Beyene; Workineh, Meseret; Gedefaw, Lealem
Abstract : Background. Reference values for the CD3 +, CD4 +, CD8 +, and CD4 + to CD8 + ratio T lymphocyte subsets are adopted from textbooks. But for appropriate diagnosis, treatment, and follow-up of patients, correct interpretations of the laboratory results from normal reference interval are mandatory. This study was, therefore, planned to establish normal reference interval for T lymphocytes subset count and CD4 + to CD8 + ratio. Methods. A cross-sectional study was conducted on apparently healthy adult individuals who visited voluntary counseling and HIV testing clinic Gondar University Hospital from April to May, 2013. Whole blood was analyzed using fluorescence-activated cell sorting (BD FACS, San Jose, CA) machine to enumerate the T-cell subpopulations. Results. Out of the total 320 study participants, 161 (50.3%) were men and 159 (49.7%) were women. The normal reference intervals were (655–2, 823 cells/ μ L), (321–1, 389 cells/ μ L), and (220–1, 664 cells/ μ L) for CD3 +, CD4 +, and CD8 + T lymphocyte subsets, respectively, and CD4 + to CD8 + ratio was 0.5–2.5. Conclusion. The overall CD3 + T lymphocytes reference interval in the current study was wide; low CD4 + T lymphocytes, CD4 to CD8 ratio, and high CD8 + T lymphocytes values were observed.